2016
DOI: 10.1111/ens.12167
|View full text |Cite
|
Sign up to set email alerts
|

Host range of braconid species (Hymenoptera: Braconidae) that attack Asphondyliini (Diptera: Cecidomyiidae) in Japan

Abstract: We reared six idiobiont braconids, Bracon asphondyliae, B. sunosei, B. tamabae, Simplicibracon curticaudis, Testudobracon longicaudis and T. pleuralis from 22 identified species and 11 unidentified segregates of Asphondyliini (Diptera: Cecidomyiidae) in Japan. A total of 22 cecidomyiid species and segregates were newly recorded as hosts of the braconids. Analysis of cytochrome oxidase subunit I (COI) did not show any evidence of host races among the braconids. Bracon sunosei, which was synonymized with B. asph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In sub-Saharan Africa, B. celer has been reported in Kenya, Ethiopia, Namibia, and South Africa (Silvestri 1913(Silvestri , 1915Neuenschwander 1982;Mkize et al 2008;Daane et al 2011). The genus was previously found to be monophyletic with high statistical support, using 658 bp COI sequences (Matsuo et al 2016). Our NJ and ML analyses recovered B. asphondilae and B. tamabae as non-monophyletic with low statistical support, probably due to the shorter COI region utilized (547 bp).…”
Section: Braconidaementioning
confidence: 65%
“…In sub-Saharan Africa, B. celer has been reported in Kenya, Ethiopia, Namibia, and South Africa (Silvestri 1913(Silvestri , 1915Neuenschwander 1982;Mkize et al 2008;Daane et al 2011). The genus was previously found to be monophyletic with high statistical support, using 658 bp COI sequences (Matsuo et al 2016). Our NJ and ML analyses recovered B. asphondilae and B. tamabae as non-monophyletic with low statistical support, probably due to the shorter COI region utilized (547 bp).…”
Section: Braconidaementioning
confidence: 65%
“…xylostella (Arvanitakis et al 2014). On the other hand, recent studies have revealed that the host ranges of idiobiont ectoparasitoids, such as Bracon and Habrobracon species (Braconidae), are narrower than that expected previously (Chomphukhiao et al 2018;Matsuo et al 2016). Host specificity of parasitoids in relation to koinobiosis or idiobiosis will be a challenging issue to be discussed again.…”
Section: Discussionmentioning
confidence: 92%
“…In I. yukawai , however, B. tamabae , the most dominant parasitoid, is a polyphagous and multivoltine ectoparasitoid (idiobiont) (Matsuo et al. ). Therefore, it does not need to enter diapause to synchronize its lifecycle with that of the host gall midge.…”
Section: Discussionmentioning
confidence: 99%
“…Bracon tamabae Maeto (Hymenoptera: Braconidae) has been known as an ectoparasitoid of mature larvae and pupae of I. yukawai (Matsuo et al. ). This parasitoid is polyphagous, attacking other gall midges of Asphondyliini, such as Asteralobia sasakii (Monzen), A. soyogo (Kikuti), D. machilicola and P. neolitseae , of which the last two species occasionally coexist in broad‐leaved evergreen forests.…”
Section: Methodsmentioning
confidence: 99%